Alexander and the Terrible, Horrible, No Good, Very Bad Day - Dorsey, Kerris; 1998-; Mullally, Megan; Coolidge, Jennifer; Thorne, Bella; 1997-; Van Dyke, Dick; Viorst, Judith; 1996-; Minnette, Dylan; 1973-; Levy, Shawn; et al. (Burbank, CA, 2015)
It follows the exploits of eleven-year-old Alexander as he experiences the most terrible and horrible day of his young life, a day that begins with gum stuck in his hair, followed by one calamity after another. But when Alexander tells his upbeat family about the misadventures of his disastrous day, he finds little sympathy and begins to wonder if bad things only happen to him.
Keywords: Drama; Families; Drama; Boys; Juvenile drama; Drama; Families; Drama; Boys; Juvenile drama; Families; Boys